Single-center experience with ultra-early cranioplasty within 3 weeks after decompressive craniectomy - Lei Zhao; Gengshen Zhang; Xiaomeng Liu; Lijun Yang; Kai Tang; Jianliang Wu (Frontiers in Neurology)
BackgroundThe optimal timing of cranioplasty (CP) after decompressive craniectomy (DC) is inconclusive. This article aims to investigate the effect of different timing of CP on the neurologic prognosis of patients, and to explore the feasibility and safety of ultra-early CP (within 3 weeks) following DC.MethodsThe duration time of surgery, intraoperative bleeding volume, surgery-related complications, and activities of daily living (ADL) scores were retrospectively analyzed in 23 patients underwent ultra-early CP performed within 3 weeks, and compared with 136 patients with non-ultra-early CP performed within the same time period.ResultsThe mean duration time of surgery in the ultra-early group was significantly shorter than that in the non-ultra-early group. ADL scores were significantly lower in the ultra-early group than in the non-ultra-early group both before and 1 month after CP, but there was no statistically significant difference in ADL scores between the two groups at long-term follow-up. The overall incidence of surgery-related complications was 17.39% (4/23) in the ultra-early group and 14.71% (20/136) in the non-ultra-early group, and there was no statistically significant difference in the comparison between the two groups (p = 0.739).ConclusionBoth ultra-early and non-ultra-early CP can significantly improve the neurological prognosis of patients. Ultra-early CP can significantly shorten the length of surgery and does not increase the incidence of surgery-related complications, which has a certain degree of safety and feasibility, and can be popularized under the premise of strict screening of indications, but further research is still needed.